Robustness of Empirical Evidence for the Democratic Peace: A Nonparametric Sensitivity Analysis. (2021) - Imai, Kosuke; Lo, James
Abstract: The democratic peace—the idea that democracies rarely fight one another—has been called "the closest thing we have to an empirical law in the study of international relations." Yet, some contend that this relationship is spurious and suggest alternative explanations. Unfortunately, in the absence of randomized experiments, we can never rule out the possible existence of such confounding biases. Rather than commonly used regression-based approaches, we apply a nonparametric sensitivity analysis. We show that overturning the negative association between democracy and conflict would require a confounder that is forty-seven times more prevalent in democratic dyads than in other dyads. To put this number in context, the relationship between democracy and peace is at least five times as robust as that between smoking and lung cancer. To explain away the democratic peace, therefore, scholars would have to find far more powerful confounders than those already identified in the literature.